Engineering Women: Re-visioning Women's Scientific Achievements and Impacts - Tietjen, Jill S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Packed with fascinating biographical sketches of female engineers, this chronological history of engineering brightens previously shadowy corners of our increasingly engineered world's recent past. In addition to a detailed description of the diverse arenas encompassed by the word 'engineering' and a nuanced overview of the development of the field, the book includes numerous statistics and thought provoking facts about women's roles in the achievement of thrilling scientific innovations. This text is a unique resource for students launching research projects in engineering and related fields, professionals interested in gaining a broader understanding of how engineering as a discipline has been impacted by events of global significance, and scholars of women's immense, often obscured, contributions to scientific progress. Illuminates the many significant contributions of women in engineering Educates readers about the evolution of the field of engineering over the last century Demonstrates how key engineering advances are driven by socio-economic and cultural contexts.
Introduction -- The Early Days of Engineering -- Women Can be Engineers, Too! -- War's Unintended Consequences -- Suburbia and Sputnik -- Bridges to the Future -- Bridges to the Future.
Keywords: Technology -- Sociological aspects; Science -- History; Engineering; Life sciences; Social sciences; Humanities; Science; Science, Technology and Society; History of Science; Technology and Engineering; Life Sciences; Humanities and Social Sciences; Physical Sciences